Параметричний синтез нечіткого регулятора системи керування паровою турбіною атомної електростанції - Федянина, Х. Б.; Северин, В. П. (Видавництво Львівської політехніки, 2011)
This paper describes solution of synthesis problems in intellectual control systems. Optimal control systems with fuzzy controllers were synthesized for steam turbine, thus allowing comparison between fuzzy controllers and traditional PID controllers.
Keywords: парова турбіна; нечітка логіка; система керування; регулятори частоти; параметричний синтез